2019
DOI: 10.1002/jsfa.10147
|View full text |Cite
|
Sign up to set email alerts
|

The impact of grapevine red blotch disease on Vitis vinifera L. Chardonnay grape and wine composition and sensory attributes over three seasons

Abstract: BACKGROUND: Grapevine red blotch virus (GRBV) is a recently discovered DNA virus, which was demonstrated to be responsible for grapevine red blotch disease (GRBD). Its presence has been confirmed in the United States, Canada, Mexico, and South Korea in white and red Vitis vinifera cultivars, including Chardonnay. It has been shown that the three-cornered alfalfa treehopper (Spissistilus festinus) was able to both acquire the GRBV from a grapevine infected and transmit it to healthy grapevines in glasshouse con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 43 publications
(61 reference statements)
0
19
0
Order By: Relevance
“…Detrimental effects of red blotch disease are similar to GLRD. GRBaV affects berry physiology, causing uneven ripening, higher titratable acidity, and lower anthocyanin and sugar content ( Girardello et al, 2019 , 2020 ; Rumbaugh et al, 2021 ) putatively due to an impairment of carbon import into the berry ( Martínez-Lüscher et al, 2019 ). Rumbaugh et al (2021) observed a general decrease of fruity aroma compounds in Cabernet Sauvignon, mostly linked to a reduction of monoterpenes, such as limonene, ß-myrcene, α-terpinene, geranial, and p-cymene.…”
Section: Virus Infectionsmentioning
confidence: 99%
“…Detrimental effects of red blotch disease are similar to GLRD. GRBaV affects berry physiology, causing uneven ripening, higher titratable acidity, and lower anthocyanin and sugar content ( Girardello et al, 2019 , 2020 ; Rumbaugh et al, 2021 ) putatively due to an impairment of carbon import into the berry ( Martínez-Lüscher et al, 2019 ). Rumbaugh et al (2021) observed a general decrease of fruity aroma compounds in Cabernet Sauvignon, mostly linked to a reduction of monoterpenes, such as limonene, ß-myrcene, α-terpinene, geranial, and p-cymene.…”
Section: Virus Infectionsmentioning
confidence: 99%
“…Secondary berry metabolites can also be influenced by GRBD. It has been reported that grapes from symptomatic red blotch disease grapevines were lower in total soluble solids, flavan-3-ol, and total phenolic content and higher in the flavonol content when compared to grapes from healthy, GRBV-negative grapevines [ 10 ]. Enzyme activities involved in core phenylpropanoid, stilbene, flavonoid, and anthocyanin biosynthetic pathways are reduced in GRBV-positive berries at ripening stages [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…GRBD can also affect the wine volatile composition and change wine quality. Girardello et al [ 10 ] found wines produced from GRBV-positive vines had lower levels of α-terpinene, p-cymene, linalool, and limonene than wines created with grapes from healthy, GRBV-negative vines. Since linalool and limonene concentrations accumulate in grapes and reach the maximum levels at later stages of ripening [ 16 ], it is possible that the lower levels of linalool and limonene in wines were caused by the delayed accumulation of those compounds in the grapes due to GRBV.…”
Section: Introductionmentioning
confidence: 99%
“…For example, leaves on infected vines show increased levels of sugar, phenolics, particular amino acids, and enzymatic activity related to plant defense, as well as a reduction in carbon fixation [ 16 , 17 , 18 ]. However, the most damaging are the effects on grape composition [ 17 , 18 , 19 , 20 ] which has been shown to be detrimental to final wine quality [ 21 ]. GRBV delays ripening by decreasing the accumulation of sugar and anthocyanin in berries, potentially due to the impairment of translocation mechanisms [ 17 , 18 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…GRBV delays ripening by decreasing the accumulation of sugar and anthocyanin in berries, potentially due to the impairment of translocation mechanisms [ 17 , 18 , 20 ]. The virus has variable impacts on primary and secondary metabolites, specifically phenolic and aroma compounds [ 17 , 19 , 20 ]. In summary, detrimental economic impacts to vineyards in the United States could reach $68,548/ha with vine removal being the only current method of alleviation [ 22 ].…”
Section: Introductionmentioning
confidence: 99%